1992
DOI: 10.1007/bf00198034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of solute/proton cotransport in plasma membrane vesicles from Ricinus cotyledons, and a comparison with other tissues

Abstract: Plasma membrane vesicles, purified by aqueous two-phase partitioning, were used to investigate the presence of sugar and amino acid carriers in cotyledons and roots of Ricinus communis L. and in roots of red beet (Beta vulgaris L.). Artificial pH and electrical gradients were generated across the plasma membrane, and [(14)C]acetate and [(14)C]tetraphenylphosphonium were used to demonstrate the presence of an internal alkaline pH gradient and an internal negative membrane potential, respectively. In Ricinus cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Both transporters are also sensitive to SH group inhibitors such as N-ethylmaleimide (NEM) or p-chloro-mercuriphenylsulphonic acid (PCMPS) which has already been described by various authors (Table 4; Delrot and Bonnemain, 1981 ;Williams et aL, 1992).…”
Section: Substrate Specificity and Sensitivity To Inhibitors And Ph mentioning
confidence: 88%
“…Both transporters are also sensitive to SH group inhibitors such as N-ethylmaleimide (NEM) or p-chloro-mercuriphenylsulphonic acid (PCMPS) which has already been described by various authors (Table 4; Delrot and Bonnemain, 1981 ;Williams et aL, 1992).…”
Section: Substrate Specificity and Sensitivity To Inhibitors And Ph mentioning
confidence: 88%
“…It has previously been found that while NEM inhibits solute transport in intact tissue, it has no effect on uptake into castor bean plasma membrane vesicles. It has been suggested that in castor bean there is little direct effect on the permease but, rather, the response is due to an indirect effect on the driving force (Williams et al, 1992;Weston et al, 1994). The His modifier DEPC has been shown to inhibit amino acid uptake into plasma membrane vesicles (Li and Bush, 1990;Weston et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Transport of solutes across cell membranes is fundamental to this process of partitioning. Studies in castor bean (Ricinus communis) have suggested that transport of amino acids across the plasma membrane is mediated by specific transporters driven by the proton electrochemical gradient (Williams et al, 1992(Williams et al, , 1996Weston et al, 1994Weston et al, , 1995. Our previous studies in roots of castor bean using isolated membrane vesicles indicated that several different amino acid transporters exist (Weston et al, 1995).…”
mentioning
confidence: 97%
“…Phase-partitioned plasma membrane was prepared according to a modification of the method described by Williams et al (1992). Red beet microsomal protein (33-35 mg) was suspended in 1.6 cm3 of phase suspension medium containing 250 mo1 m-3 sorbitol, 5 mo1 m-3 potassium phosphate buffer (pH 7.0), and 1 mo1 m-3 DTT.…”
Section: Aqueous Two-phase Partitioning Of the Microsomal Fractionmentioning
confidence: 99%